Growth and Performance of Indian Fish and Fishery Products Exports - Radhakrishnan, K.; Tesfom, M. A.; Krishnan, M.; Infantina, J. Amali; Sivaraman, I. (Fishery Technology, 2018)
This study profiles the growth and instability of theIndian fish and fishery products export and itsperformance over the past five decades. The resultsshow that growth rates of seafood exports has beenincreasing, though the instability increased. Thepossible reason for the growth and instability ofIndian fish and fishery exports have also beendiscussed in this study.